Peranan Gembala Sidang bagi Pertumbuhan Jemaat di Gereja Lokal - Indratno, Yohanes Twintarto Agus; Dully, Stefanus; Harianto, Yusup Heri (Jurnal Salvation, 2022)
Abstract: The shepherd is the one who guides the congregation in pastoralism, certainly too short to teach how broad and deep the knowledge of God is. One of the most important things is that God Himself has laid down the task of caring for, nurturing, and educating the congregation into His power and calling. Shepherds who must prepare the congregation to live in favor of God. The purpose of this study is to explain the duties and roles of shepherds in faith-building or the so-called discipleship. Discipleship is a command of God called the great commission in Matthew 28:19 it says "Make all nations my disciples." in discipleship lessons is to "know God and become disciples of Christ. Therefore, a person who has received Jesus Christ must be immediately discipled, so that his character is immediately formed towards a better direction and a skill in serving so as to have a knowledge of the truths of God's Word. The method used in the research is a qualitative description (case study) of the role of the shepherd in leading the congregation to be more effective. The shepherd's job in serving the congregation is to "nurture believers and unbelievers to grow up in the faith and become disciples of the Lord Jesus. Being a disciple of the Lord Jesus is a command that the Shepherd must work on, therefore the shepherd must have a knowledge of God's Word, an understanding of the basics of the Christian faith, character building, and the gift of serving. Abstrak: Gembala adalah orang yang membimbing jemaat dalam penggembalaan, adalah tugas yang cukup berat karena membimbin, merawat, mengasuh, dan mendidik jemaat adalah tugas gembala yang mulai dan agung. Tujuan dari penelitian ini adalah untuk menjelaskan tugas dan peran gembala dalam pembinaan iman atau yang disebut pemuridan. Pemuridan adalah perintah Allah yang disebut amanat agung dalam Matius 28:19 dikatakan “Jadikanlah semua bangsa muridKu.” dalam pelajaran pemuridan adalah “mengenal Allah dan menjadi murid Kristus. Oleh sebab itu, seorang yang telah menerima Yesus Kristus harus segera dimuridkan, agar karakternya segera dibentuk menuju ke arah yang lebih baik serta kecakapan dalam melayani sehingga memiliki pengetahuan tentang kebenaran-kebenaran Firman Tuhan. Metode yang digunakna dalam peneltian adalah kualitatif deskripsi (studi kasus) tentang peran gembala dalam memimpin jemaat supaya lebih efektif. Tugas gembala dalam melayani jemaat adalah“membina orang percaya maupun orang yang belum percaya supaya semakin bertumbuh dewasa dalam iman dan menjadi murid Tuhan Yesus. Menjadi murid Tuhan Yesus adalah perintah yang harus dikerjakan oleh Gembala, oleh karena itu gembala harus memiliki pengetahuan tentang Firman Tuhan, pengertian tentang dasar-dasar iman Kristen, pembentukkan karakter, dan karunia untuk melayani.